FRI0043 Trends in all-cause and cardiovascular mortality in patients with rheumatoid arthritis. a 10- to 20-year follow-up study in 3 consecutive incidence cohorts. (12th June 2018) - Provan, S.A.; Lillegraven, S.; Haavardsholm, E.A.; Kvien, T.K.; Sexton, J.; Uhlig, T.
Abstract : Background: The mortality rate in patients with rheumatoid arthritis (RA) has been estimated to be 1.5–1.6 compared to the general public. Moreover, RA patients are still not benefitting fully from the declining mortality rate that the general population has enjoyed and cardiovascular disease (CVD) continues to be a major concern. Objectives: To examine the all-cause and CVD mortality in 3 consecutive cohorts of patients with incident RA, compared to population controls Methods: The Oslo RA register (ORAR) was established in 1994. The inclusion criteria were a diagnosis of RA according to the 1987 ACR criteria and residency in Oslo. The register was updated annually until 2009, and validated for completeness. 1 In January 2012, 3328 patients were registered in ORAR. We grouped patients into 3 successive incidence cohorts; 1996(1994–1998), 2001 (1999–2003) and 2006(2004–2008). For each patient we identified 5 historical population controls matched according to age at disease incidence, gender and postal code of residence. Patients and controls were linked to the Norwegian Cause of Death Registry. Counts were compared using chi 2 tests. The hazard ratio (HR) for survival was calculated using stratified cox-regression models adjusted for highest achieved level of education. Results: 422, 477 and 459 patients in the 1996, 2001 and 2006 cohorts were matched to 2110, 2385 and 2295 controls respectively. 20, 15 and 10 years follow-up for 1996, 2001 and 2006 cohorts were available in 201, 292 and 311 patients respectively. Results are presented in the table 1. Conclusions: RA patients with disease incidence in the period 1994–2003 had increased all-cause and CVD related mortality after 10–15 years of disease duration, compared to the population of Oslo. The increased mortality was not observed in the 2004–2008 cohort. Improved survival in recent years may be related to more effective therapies and earlier diagnosis, but further analyses are warranted. Reference: [1] Kvien, Uhlig. J Rheumatol2004. Disclosure of Interest: None declared